PENGARUH PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN NON MEDIS PADA RSIA ERIA BUNDA PEKANBARU - Sri Riski Herani; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The purpose of this study was to determine the effect of job training and work motivation on the performance of non-medical employees at RSIA Eria Bunda Pekanbaru. The sampling technique used the census method, which used all the population as samples, namely 57 respondents from non-medical employees of RSIA Eria Bunda Pekanbaru. This study uses a descriptive type of research with a quantitative approach. The dependent variable (Y) in this study is employee performance. The independent variables (X) include job training (X1) and work motivation (X2), for the data processing program using IBM SPSS 21.0 statistics. The results of this study indicate that partially job training has a positive and significant effect on employee performance on the results of the T-test10.169 > T table 2.005and the variable of work motivation has a positive and significant effect on employee performance, the results of the T test count 11,094 > T table 2,005. Meanwhile, simultaneously, the variables of job training and work motivation have a significant effect on employee performance with F count 71,957 > F table 3.172. The influential variable is the most dominant work motivation.Keywords: Job training, , Work Motivation and Employee Performance.